Pedagogical Mechanisms for Preparing Future Education Managers for Administrative Activities to Support Quality Education in the Sustainable Development Goals (SDGs) Era - Dustnazar Omonovich Khimmataliev; Nilufar Pardaqizi Omonova; Hasan Nematovich Bozorov; Munisa Aminovna Davlatova; Shoira Isajanovna Abdullayeva; Lola Muhiddinkizi Sunnatova; Xoshimjon Abdumalikovich Mamajonov; Zakiya A. Narimbetova (ASEAN Journal of Educational Research and Technology, 2026)
This study seeks to enhance the managerial readiness of future education professionals through structured pedagogical processes. An experiment with experimental and control groups was conducted, both receiving identical content but different teaching strategies. The developed model combined conceptual, technological, and reflective components, supported by digital tools and project-based learning. Results showed that students in the experimental group demonstrated stronger competence in planning and managing educational activities. This improvement stemmed from structured, goal-oriented experiences reinforced by formative evaluation. By integrating strategic management with pedagogical conditions, the model encouraged autonomy and reflective thinking. The findings emphasize the value of targeted pedagogical interventions in preparing competent education managers. Moreover, the study contributes to Sustainable Development Goals (SDGs), particularly in advancing quality education through innovative approaches to professional training.